The Effect of Different Tread Profiles on Pullout Strength of Glass Fiber Reinforced Polymer Composite Materials - Ünal, Engin (My University, 2018)
Recently, the usage of polymer composite materials has been increased significantly. Glass fiberreinforced polymer (GFRP) composite materials are preferred for different areas such as aviation, railway, energy,defense and so on due to their high thermal and tensile strength. The most common methods for joining compositemachine parts are bolts and rivets, etc. In this study, Pullout tests were performed with metric, knuckle, buttress,trapezoid and square profile screws to determine the effect of different screw threads on the pullout force. Thebolts were taken to have a diameter of 16 mm and feed of 2 mm. In addition, a finite element model was createdfor determining the von-Mises equivalent stresses and total deformation. The metric thread profile gave the bestresults both in FEA and in experimental studies. The numerical and experimental results were in a good agreementcould be concluded.
Keywords: Malzeme Bilimleri; Kompozitler